2015
DOI: 10.1111/bjh.13654
|View full text |Cite
|
Sign up to set email alerts
|

The utility of ADAMTS13 in differentiating TTP from other acute thrombotic microangiopathies: results from the UK TTP Registry

Abstract: SummaryThrombotic microangiopathies (TMAs) are frequently difficult to differentiate clinically, and measurement of ADAMTS13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13) remains vital in thrombotic thrombocytopenic purpura (TTP) diagnosis. We retrospectively reviewed cases referred for ADAMTS13 testing, using UK TTP Registry screening data. Of a total 810 cases, 350 were confirmed as TTP. The 460 non-TTP cases comprised secondary TMAs (24Á57%) and haemolytic uraemic syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 15 publications
1
58
1
Order By: Relevance
“…Subsequently, a FRETS‐based assay utilizing the VWF73 substrate was used for all assays performed at both laboratories. Severe deficiency in ADAMTS13 was defined as an activity level of not more than 10% based on previous work indicating that this cutoff provides excellent sensitivity and specificity for idiopathic TTP …”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, a FRETS‐based assay utilizing the VWF73 substrate was used for all assays performed at both laboratories. Severe deficiency in ADAMTS13 was defined as an activity level of not more than 10% based on previous work indicating that this cutoff provides excellent sensitivity and specificity for idiopathic TTP …”
Section: Methodsmentioning
confidence: 99%
“…delirium, seizures). It has been suggested that more severe thrombocytopenia (platelet count <30 × 10 9 /L) and milder renal impairment (serum creatinine <200 μmol/L) may help to distinguish TTP from aHUS but these criteria are neither sensitive nor specific . Rather, TTP is defined by severely reduced (<10%) activity of the von Willebrand factor (vWF)‐cleaving protease, ADAMTS13.…”
Section: Causes Of Tmamentioning
confidence: 99%
“…TTP is a rare disorder with an incidence of four to 11 patients per 10 6 per year . In the past, many patients with thrombocytopenia and features of TMA were misdiagnosed with TTP, and some were subjected to a trial of TPE involving, by definition, large‐volume plasma transfusion. Clarification in 1998 that a sine que non for the diagnosis of TTP is severe deficiency of ADAMTS13 has allowed a more systematic approach to this situation.…”
Section: Discussionmentioning
confidence: 99%